PENGARUH PENERAPAN STRUKTUR DAN PROSES SISTEM PENGENDALIAN MANAJEMEN TERHADAP KINERJA MANAJERIAL DENGAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI VARIABEL INTERVENING (Studi Pada RSUD dr. R. Soetrasno Rembang) - Nugroho, Rion Fiarta Adi; Hidayat, Riskin (JAB (Jurnal Akuntansi & Bisnis), 2015)
This research aims to test the effect of the applying structure and process management control to management performance through responsibility accounting in RSUD dr. R. Soetrasno Rembang. This research use survey with purposive sampling method. This sampel is 31 respondents consisting of a cashier, finance, planning section, and structural labour. Data were collected by means of questionnaires directly deliver to respondents. Analysis of the data using path analysis. This research suggest that structure and process management control influence positive not significant to management performance, and than responsibility accounting influence positive significant to management performance. This is suggest that responsibility accounting indirectly can mediate the relationship between structure management control with management performance. Morever, this research also refer that the responsibility accounting can’t mediate the relationship between process management control with management performance. Keyword:             Structure and Process Management Control, Management Performance, Responsibility Accounting.